The role of perceptions about trade and inequality in the backlash against globalization - Barbara Dluhosch (SN Business & Economics, 2021)
Many countries in the Western hemisphere are experiencing a political backlash against globalization. When explaining this phenomenon, much of the extant research draws on the distributional effects of international competition, in particular the opposition to trade by those who are adversely affected. Using cross-sectional data on subjective well-being from the World Values Survey and the European Values Study and combing these self-reports with trade and incomes data, this paper contributes to this strand of research by focusing on the subjective element in the formation of anti-trade sentiments. It thus explores how the role of international trade in the income distribution is being perceived at the individual level. Simulations based on the data reveal that matters of income inequality are evaluated differently, depending on how deeply the respective economy is integrated into world markets: results suggest that the extent of trade globalization amplifies any negative effect of income inequality on subjective well-being. If the role of international openness in the income distribution is perceived to be more pronounced than it actually is, the subjective element has wider politico-economic implications; it carries the risk of costly anti-trade policies without necessarily narrowing the income distribution.
Keywords: 330; Perceptions; Income distribution; International trade; Protectionism; Globalization